Production of amorphous silica from rice husk in fluidised bed system - Ngo, Saik Peng (2006)
Conventional methods for the preparation of amorphous silica (SiO2) are very energy-intensive and expensive. Amorphous silica has wide industrial applications, with annual world consumption in the excess of 1 million tonnes valued at RM4,500 per tonne. Rice husk ash contains amorphous silica in the excess of 95 wt%. Thermal treatment of rice husk is deemed the most economical method to recover this amorphous silica from the readily available rice husk (approximately 0.5 million tonnes per annum in Malaysia). Hence, the purpose of this research was to recover amorphous silica from rice husk through thermal treatment in fluidised bed system. Experimental works were conducted in fluidised bed combustor systems to determine the optimum mixing parameters (sand size, fluidising velocity, static bed height) and combustion parameters (temperature, air supply, rice husk moisture content, feeding design) to produce amorphous, carbon-free silica from rice husk. The fly and bottom ashes were analysed for their residual carbon contents and silica structures through loss on ignition (LOI) tests and X-Ray Diffraction (XRD) analyses, respectively. Computational fluid dynamics (CFD) modelling using FLUENT was also conducted to optimise the fluidised bed design and to overcome problems encountered in experimental works. Experimental results showed that amorphous, siliceous ash with residual carbon content of down to 1.0 wt% could be obtained by burning water-washed rice husk that was free from alkali metal compounds (potassium oxide and sodium oxide). The short freeboard height of the experimental fluidised bed resulted in the incomplete oxidation of carbon and sand contamination in the ash. Modelling results showed that both problems could be overcome by increasing the height of the fluidised bed to 5000mm. In addition, the induction of swirling flows at the freeboard region was found to be beneficial in increasing the residence time of ash in the combustor, leading to higher carbon burnout